CAREER CHOICE MOTIVATIONS OF UNIVERSITY STUDENTS IN TUNISIA - Khanchel, Hanen (The journal of contemporary issues in business and government, 2022)
This article is based on asociological framework and data collection from Tunisian students in the commercial and administrative affairs in order to analyze their priority motivations for career choice. We take a particular interest in the study of motivations in responsibility and professional representation in this field, these learners will be the guarantors of the faithful image, of objectivity of reporting and ethical behavior. The study was descriptive in nature and it employed a mixed methods design. Combining qualitative and quantitative approaches. The study had a sample of 50 respondents who were purposively selected. An empirical hierarchy of motivations shows that the interest of these participants to choose a speciality is certainly to advance the cause in which they are involved, but the primary source of motivation is first and foremost their career development. In the majority of cases, motivation is an integral part of their career, while in other cases, interest for commercial and administrative fieldserves to build up social capital that can be used later in their job.However, our results are quite far from thisreality: students show themselves to be more focused on the promise of rapid integration or that of attractive remuneration offered by the commercial and administrative affairs specialty of than on the regulated aspect represented by the profession.Theoretical and managerial implications are advanced highlighting the human, technological and relational sides of the study.